A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Encapsulated tannic acid protects against ETEC-induced intestinal damage via modulating gut microbiota and barrier function - Hang Gao; Ying Xiao; Tianjiao Wang; Ruohan Liu; Qiao Li (Food Research International, 2026)

Emulsion gels stabilized by millet chaff prolamin–gallic acid or –sucralose conjugates: characterization, application in curcumin, and mechanism insights - Yan Li; Jie Liu; Hao Wang; Biao Ma; Zihao Zhang; Ling Dang; Yajun Zheng; Ruohan Liu; Yi Li (Food Chemistry, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Toxoplasma gondii infection reduces CD59 expression through downregulation of JAK2/STAT3 signaling axis to enhance decidual NK cell cytotoxicity via the RAS/MAPK pathway - Shuyan Wang; Luyun Huo; Yan Zou; Ruohan Yang; Xiao Wang; Haixia Zhang; Liqin Ren; Jing Yang; Jie Li; Xuemei Hu; Yushan Ren (Inflammation Research, 2026)

Spectral-enhanced cross-domain network: a novel daily runoff prediction model based on energy amplification and cross-domain multi-scale collaboration - Ruohan Wang; Tao Yang (Journal of Hydrology, 2026)

Metal complexation-triggered chromogenic reaction and fluorescence response: A universal dual-mode sensing strategy for fast visualization of heavy metal ions - Shuangshou Wang; Zan Wang; Ruohan Xu; Cheng Cheng; Yujun Zhong; Jia Yang; Mingfu Ye; Jinying Chen; Yuxi Gu; Jingchong Yan (Environmental Research, 2026)

Heat transfer and dynamic behavior of wall-adhered carbon dioxide droplets: power-law correlation and the cryogenic ring effect - Qifan Wang; Minyun Liu; Yanping Huang; Shanfang Huang; Ruohan Zheng; Houjun Gong (Annals of Nuclear Energy, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Chemical reaction kinetics regulated dual-signal sensing system for discriminating EV-A71 and CV-A16 - Tongtong Ye; Wenjing Xu; Ruohan Tang; Yuhan Wang; Yang Li; Xuming Zhao; Hui Zhang; Lihua Chen (Analytica Chimica Acta, 2026)

Analysis of spatial heterogeneity and influencing factors of carbon emission efficiency at the provincial level in China based on machine learning - Xinglan Dai; Ruohan Zhang; Zishuai Zu; Ying Wang (Journal of Environmental Management, 2026)

Construction of electrochemical dual‑carbon-membrane reactor with nitrogen-doped carbon membranes for synergetic dimethylacetamide degradation and ion removal via capacitive deionization: Insights into proton exchange membrane-mediated charge compensation and operational stability - Yuxuan Zhu; Hanlin Wang; Ruohan Wang; Haikuo Lei; Heli Zhao; Huichao Su (Chemical Engineering Journal, 2026)

Metal-free C H functionalization unlocks multifunctional luminescent PEGs for biomedical imaging and therapy - Weiping Liu; Qinyue Guo; Lifang Ma; Ruohan Li; Jiajia Ren; Haixia Jiang; Gang Wang; Rong Zeng (Chemical Engineering Journal, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Conversion of wheat straw by black soldier fly larvae and fertilization effects of frass - Xifeng Wang; Ruohan Wang; Junzhao Wei; Rui Hu; Ziling Wang; Haifeng Li; Pengxiao Chen; Jianhang Qu; Mingjun Li (Journal of Asia-Pacific Entomology, 2026)

Co-exposure to multiple fine particulate matter constituents and adults obstructive sleep apnoea (OSA) in Southern China - Suhan Wang; Gongbo Chen; Peipei Dong; Hailin Xiong; Yuewei Liu; Ruohan Zhou; Ranxu Zhang; Qiong Ou (Environmental Pollution, 2026)

Wind-driven variability in phytoplankton dynamics in a semi-enclosed sea - Ruohan Sun; Xinyi Kang; Zhen Wang; Haibo Zhang; Hang Yin (Estuarine, Coastal and Shelf Science, 2026)

A probabilistic framework for predicting spatiotemporal intensity and variability of outdoor thermal comfort - Shisheng Chen; Ruohan Xu; Nyuk Hien Wong; Shanshan Tong; Jiashuo Wang; Matthaios Santamouris (Building and Environment, 2026)

Facile synthesis of palladium nanoparticles loaded on zirconia/porous carbon nanocomposites via a ternary synergistic strategy for ultrasensitive adrenaline detection - Rou Wang; Lin Hao; Ruohan Yang; Hongyuan Yan; Penglian Ma; Yufan Zhang (Analytica Chimica Acta, 2026)

A novel TpAQ-COF/ZnS/ZnIn2S4 ternary photocatalyst with double Z-scheme heterostructure for visible light photocatalytic degradation of 2,4-dichlorophenol - Ruohan Sun; Yuqing Xia; Tingting Ma; Hui Yu; Guixia Liu; Jinxian Wang; Wensheng Yu; Feng Sun; Xiangting Dong (Journal of Cleaner Production, 2026)

Gallic acid-reinforced Rana chensinensis ovum protein isolates-Gellan gum thermally reversible emulsion gel: Insight of the structure and potential applications in dysphagia management - Ruixue Liu; Min Gao; Li Zhang; Shihan Wang; Ying Yang; Jing Bai; Ruohan Wang; Yongsheng Wang; Zhihan Wang (Food Research International, 2025)

Rice protein-based gel particles for Pickering emulsion - Peifeng Lv; Qianyu Ye; Yong Wang; Like Mao; Ruohan Yu; Cordelia Selomulya (Food Hydrocolloids, 2025)

Carbon dioxide bubble dynamics and wall heat transfer in flash chambers: Nucleation departure and cold bubble effects - Qifan Wang; Yansong Han; Ailing Fu; Shanfang Huang; Ruohan Zheng; Yanping Huang; Houjun Gong (Annals of Nuclear Energy, 2025)

Hydrophobic magnetic deep eutectic solvents: An all-in-one platform for fast visualization, removal, recycle and degradation of anionic dyes - Yanshang Kang; Yangrui Si; Qiwen Jin; Ruohan Xu; Yujun Zhong; Yaorui Wang; Yuxiang Fu; Jing Gu; Mingfu Ye; Shuangshou Wang (Analytica Chimica Acta, 2025)

One-step molding to prepare durable dual superlyophobic composites for non-loss mass transfer, immiscible solvent separation, and CO2 bubble removal - Chang-Lian Xu; Xingyue Wu; Yuqing Song; Jialin Liu; Ruohan Xiong; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Xin Qi; Guochun Lv; et al. (Journal of Environmental Chemical Engineering, 2025)

The global burden of pediatric respiratory infections attributable to long-term exposure to fine particulate matters - Xueqiu Ni; Ning Kang; Ke Huang; David Christiani; Hong Lu; Ting Yang; Ruohan Wang; Mingkun Tong; Tianjia Guan; Tao Xue (Environmental Pollution, 2025)

Dynamics of wall bubbles in flash evaporation systems: Heterogeneous expansion and microlayer development - Qifan Wang; Junren Hou; Shanfang Huang; Fangbei Chen; Minyun Liu; Ruohan Zheng; Yanping Huang; Lie Quan; Houjun Gong; Yu Tang (Annals of Nuclear Energy, 2025)

Long-term exposure to dust in fine particulate matter and post-stroke functional impairment—Findings from the China National Stroke Screening Surveys - Zhaoyang Pan; Xueyan Han; Man Cao; Ruohan Wang; Jian Guo; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (Journal of Hazardous Materials, 2025)

A nanofiltration and electrocatalytic membrane reactor with ozone oxidation integrated system for dyeing wastewater treatment and Na2SO4 recovery - Minghui Du; Ruohan Wang; Hong Wang; Jianxin Li (Water Research, 2025)

Carboxylesterase 1 regulates peroxisome proliferator-activated receptor gamma to inhibit the growth and metastasis of breast cancer cells - Jingli Wen; Lei Geng; Ruohan Wang; Xiaolei Zhang; Yanmin Sui; Xiaofang Liu; Xin Han (Journal of Molecular Histology, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Wood utilization and paleo-vegetation revealed by wooden remains excavated from ancient Dahe City site (AD 618–907) in Barkol, Xinjiang, northwest China - Ruohan Wang; Guilin Zhang; Yongqiang Wang; Biao Pan; Guolei Dun; Youcheng Xu; Hongen Jiang (Quaternary International, 2025)

Corrigendum to “Distribution characteristics, risk assessment, and quantitative source apportionment of typical contaminants (HMs, N, P, and TOC) in river sediment under rapid urbanization: A study case of Shenzhen river, Pearl River Delta, China” [Process Saf. Environ. Prot. 162 (2022) 155–168] - Ying Zhang; Wei Mao; Ruohan Li; Yang Liu; Peng Wang; Zelin Zheng; Yuntao Guan (Process Safety and Environmental Protection, 2025)

Paper strips-based narrowing colorimetry: An all-in-one strategy for rapid visual detection and adulteration identification of food dyes - Shuangshou Wang; Haiyang Li; Tong Li; Ruohan Xu; Chunyan Yang; Tianyou Geng; Tingxuan Yan; Qi Zhang; Daojin Li; Jingchong Yan; Yanshang Kang; Caibo Yue (Food Control, 2025)

First retrieval of 24-hourly 1-km-resolution gapless surface ozone (O3) from space in China using artificial intelligence: Diurnal variations and implications for air quality and phytotoxicity - Fan Cheng; Zhanqing Li; Zeyu Yang; Ruohan Li; Dongdong Wang; Aolin Jia; Ke Li; Bin Zhao; Shuxiao Wang; Dejia Yin; Shengyue Li; Wenhao Xue; et al. (Remote Sensing of Environment, 2025)

A novel approach to estimate land surface temperature from landsat top-of-atmosphere reflective and emissive data using transfer-learning neural network - Shuo Xu; Dongdong Wang; Shunlin Liang; Aolin Jia; Ruohan Li; Zhihao Wang; Yuling Liu (Science of The Total Environment, 2024)

Inhibitory effects of potassium sorbate and ZnO nanoparticles on Escherichia coli and Staphylococcus aureus in milk-based beverage - Yuanyuan Zhang; Qianqian Yang; Feng Lu; Xiaoyang Wang; Ruohan Liang; Xiaodan Pu; Jianlei Chen; Dahai Zhang; Zhixiang Chen; Xuzhi Zhang (International Dairy Journal, 2024)

Computational modeling of near-fault earthquake-induced landslides considering stochastic ground motions and spatially varying soil - Ruohan Wang; Guan Chen; Yong Liu; Michael Beer (Engineering Structures, 2024)

Hyaluronic acid modulates gut microbiota and metabolites relieving inflammation: A molecular weight-dependent study - Chuan Zhang; Botao Wang; Leilei Yu; Ruohan Zhao; Qingsong Zhang; Chengcheng Zhang; Shumao Cui; Jianxin Zhao; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Science Bulletin, 2024)

Operation-friendly and accurate naked-eye observation assay for fast zoonotic echinococcosis and pulmonary tuberculosis monitoring in clinics - Hong Liang; Ruohan Wang; Tianying Luo; Mengying Yuan; Xia He; Rongrong Jin; Yangyang Zhao; Rongsheng Tong; Yu Nie (Analytica Chimica Acta, 2024)

Bacteriostatic mechanism of Lactiplantibacillus plantarum CS3 cell-free supernatant of on soy sauce spoilage bacteria - Shuyu Zhang; Ruohan Yao; Qifeng Wang; Wenjun Wang; Shuoshuo Zhao; Hao Wang; Ling Zhu; Yunping Yao; Guozhong Zhao (Food Bioscience, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Peridynamics-based large-deformation simulations for near-fault landslides considering soil uncertainty - Ruohan Wang; Shaofan Li; Yong Liu; Xuan Hu; Xin Lai; Michael Beer (Computers and Geotechnics, 2024)

Unveil the potential in hydrogen activation and spillover towards NiMoS by Ni3S2 - A theoretical study - Xiaodong Liu; Hangyu He; Lijun Hu; Xiaohui Zhang; Ruohan Wang; Xuemin Yan (Fuel, 2024)

Cloud detection from Himawari-8 spectral images using K-means++ clustering with the convolutional module - Kaizheng Wang; Yitong Fu; Shunzhen Zhou; Ruohan Zhou; Gang Wen; Fangrong Zhou; Lulu Li (International Journal of Remote Sensing, 2024)

Characterization of carbonaceous particles by single particle aerosol mass spectrometer in the urban area of Chengdu, China - Junke Zhang; Rui Wang; Chunying Chen; Yunfei Su; Luyao Chen; Wei Zhang; Yingwei Xi; Yangchun Yu; Ruiyan Pu; Minghui Lu; Ruohan Wu; Xuhui Shen (Environmental Science and Pollution Research, 2024)

Identification of novel umami peptides from yeast extract and the mechanism against T1R1/T1R3 - Hao Wang; Wenjun Wang; Shuyu Zhang; Zhenhao Hu; Ruohan Yao; Hadiatullah Hadiatullah; Pei Li; Guozhong Zhao (Food Chemistry, 2023)

Adsorption and photocatalytic degradation of quinolone antibiotics from wastewater using functionalized biochar - Ning Cheng; Bing Wang; Miao Chen; Qianwei Feng; Xueyang Zhang; Shengsen Wang; Ruohan Zhao; Tao Jiang (Environmental Pollution, 2023)

Uncovering the origin of surface-redox pseudocapacitance of molybdenum phosphides enables high-performance flexible sodium-ion capacitors - Yalong Jiang; Runya Han; Jun Dong; Ruohan Yu; Shuangshuang Tan; Fangyu Xiong; Qiulong Wei; Junjun Wang; Lianmeng Cui; Haiyang Tian; Yingkui Yang; Qinyou An (Chemical Engineering Journal, 2023)

Calcium alginate-nZVI-biochar for removal of Pb/Zn/Cd in water: Insights into governing mechanisms and performance - Ruohan Zhao; Bing Wang; Pan Wu; Qianwei Feng; Miao Chen; Xueyang Zhang; Shengsen Wang (Science of The Total Environment, 2023)

Long-term exposure to the components of fine particulate matters and disability after stroke: Findings from the China National Stroke Screening Surveys - Hong Lu; Ruohan Wang; Jiajianghui Li; Mingkun Tong; Man Cao; Hengyi Liu; Qingyang Xiao; Yixuan Zheng; Yuanli Liu; Tianjia Guan; Tao Xue (Journal of Hazardous Materials, 2023)

Stillbirths attributable to open fires and their geographic disparities in non-Western countries - Tao Xue; Jiajianghui Li; Mingkun Tong; Xinguang Fan; Pengfei Li; Ruohan Wang; Yanshun Li; Yixuan Zheng; Jiwei Li; Tianjia Guan; Tong Zhu (Environmental Pollution, 2023)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

Comparison between deep learning architectures for the 1 km, 10/15-min estimation of downward shortwave radiation from AHI and ABI - Ruohan Li; Dongdong Wang; Shunlin Liang (Remote Sensing of Environment, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

Blending loss-control and normal urea maximizes nitrogen utilization of summer maize by mitigating ammonia volatilization and nitrate leaching - Wenxuan Shi; Qian Zhang; Ruohan Xie; Kai Sheng; Jinfang Tan; Yilun Wang (Plant and Soil, 2023)

Occurrence and fate of antibiotics in swine waste treatment: An industrial case - Wancen Liu; Yongfang Wang; Ruohan Xia; Xiangrui Ding; Zhicheng Xu; Guoxue Li; Long D. Nghiem; Wenhai Luo (Environmental Pollution, 2023)

Polybrominated diphenyl ethers in water, suspended particulate matter, and sediment of reservoirs and their tributaries in Shenzhen, a mega city in South China - Tingting Zhu; Youchang Zhu; Yunlang Liu; Chen Deng; Xiujuan Qi; Jinling Wang; Zhizhi Shen; Donggao Yin; Yihong Liu; Ruohan Sun; Weiling Sun; Nan Xu (Environmental Science and Pollution Research, 2023)

Recovery of nitrogen and phosphorus in wastewater by red mud-modified biochar and its potential application - Zhipeng Zhao; Bing Wang; Qianwei Feng; Miao Chen; Xueyang Zhang; Ruohan Zhao (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Morphology and mass spectrometry-based chemical profiling of peltate glandular trichomes on Mentha haplocalyx Briq leaves - Ruohan Liu; Yutuan Wang; Conglian Liang; Zhijuan Zheng; Xiuwei Du; Zhanhu Cui; Yongqing Zhang; Hongyan Liu (Food Research International, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Mechanisms of cancer cell death induction by paclitaxel: an updated review - Shuang Zhao; Yufei Tang; Ruohan Wang; Masoud Najafi (Apoptosis, 2022)

The effect of cylindrospermopsin on the bacterioplankton community: a microcosm experiment on water from Dishui Lake, Shanghai, China - Sicheng Yin; Ruohan Huang; Erik Jeppesen; Lijing Chen; Liqing Wang; Xin Fang; Wei Zhang (Journal of Oceanology and Limnology, 2022)

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Characteristics and Cause Analysis of Variations in Light Precipitation Events in the Central and Eastern Tibetan Plateau, China, During 1961–2019 - Kaifang Li; Liguo Cao; Zhengchao Zhou; Lei Jiao; Ning Wang; Ruohan Liu (Chinese Geographical Science, 2022)

Controlling factors and accumulation model of hydrocarbon reservoirs in the Upper Cretaceous Yogou Formation, Koulele Area, Termit Basin, Niger - Xuying Wang; Lunkun Wan; Zaixing Jiang; Ruohan Liu; Xiabin Wang; Wangxin Tang; Yi Gao; Shengqian Liu; Wenmao Xu (Journal of Earth Science, 2017)

Reservoir characteristics and controlling factors of Silurian Lower Kepingtage Formation in Tahe area, Tarim Basin, NW China - Ruohan Liu; Zaixing Jiang; Ming Wang; Weili Yang; Jingxiang Guo; Minghao Wu; Yi Gao; Shanyazi Wei; Zhihong Nie; Hong He (Journal of Earth Science, 2017)

Sedimentary characteristics and formation mechanisms of lacustrine beach-bars in the fourth member of the Shahejie Formation in the Shubei area, western depression of the Liaohe Oilfield, China - Yi Gao; Xiaolong Jiang; Fang Liu; Xuying Wang; Ruohan Liu (Journal of Earth Science, 2017)

miRNAs play essential roles in the floral thermogenesis of Magnolia denudata (Magnoliaceae) - Xiangyu Liu; Dechang Cao; Xiangyu Ji; Zhixiang Zhang; Yanwei Wang; Ruohan Wang (Trees, 2015)

Temperature regulation of floral buds and floral thermogenicity in Magnolia denudata (Magnoliaceae) - Ruohan Wang; Xiangyu Liu; Shulin Mou; Sai Xu; Zhixiang Zhang (Trees, 2013)